We are growing! - Keller, Laurie; Willems, Mo (Elephant & Piggie like reading!, 2016)
"Walt is not the tallest or the curliest or the pointiest or even the crunchiest. A confounded blade of grass searches for his 'est' in this hilarious story about growing up"--